2020
DOI: 10.1177/2167696820970690
|View full text |Cite
|
Sign up to set email alerts
|

“I Am Grateful That I Still Live Under One Roof With My Family”: Gratitude Among South African University Students

Abstract: During the transition from school to university, students are faced with many challenges to their well-being. This is especially true in resource constrained societies like South Africa. While there is extensive research linking well-being with gratitude, less is known qualitatively about what individuals are grateful for. A sample of 933 undergraduate students submitted gratitude lists, resulting in over 9,000 unique “gratitude items.” Thematic analysis revealed several prominent themes, such as gratitude for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…The family atmosphere can influence pro-social behavior indirectly through gratitude, supporting the previous findings ( Amaro and Miller, 2016 ; du Plessis et al, 2020 ). The results may be explained in two ways.…”
Section: Discussionsupporting
confidence: 89%
“…The family atmosphere can influence pro-social behavior indirectly through gratitude, supporting the previous findings ( Amaro and Miller, 2016 ; du Plessis et al, 2020 ). The results may be explained in two ways.…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes, this was done through modelling (especially when this perceived influence was positive) and other times through negation (the type of parent I never want to be), but it seems that for South African parents, the family of origin is an important, perhaps the most important, starting point for exploring their own parental identity. In another South African study, Du Plessis et al (2020) emphasised the gratitude for family relationships and material support among South African emerging adults.…”
Section: Discussionmentioning
confidence: 99%
“…Specific contexts such as living in transitional societies or experiencing social challenges will affect the way in which emerging adulthood and the dynamics of this phase are experienced (Landberg et al, 2019) and how the themes of instability and possibility are balanced. For example, the sociocultural context of Africa and South Africa poses unique challenges – political transition, resource constraints and an unstable economic climate might influence the identity exploration and ability of emerging adults to fulfil adult commitments (Alberts & Durrheim, 2018; Du Plessis et al 2020; Naudé, 2020; Obidoa et al, 2019; Van Lill & Bakker, 2020). Furthermore, a specific life event such as becoming a parent will also affect the way in which emerging adults, for example, focus on their development and explore their identities (Canzi et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In their research with LGBTQ+ youth, Bates et al (2020) found that social media served as a ‘safe space’ where individuals find security in community (to connect with others whose identities align with their sense of self), while also expressing narratives of individuality and autonomy. This task of balancing interpersonal relatedness and personal autonomy can be especially intricate in the South African context where emerging adults’ identity development is interwoven with interconnectedness, spirituality, and family roles and responsibilities (Du Plessis et al, 2020; Naudé & Piotrowski, 2022; Sodi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While celebrating the post-Apartheid freedom of the Rainbow Nation, they also have to contend with the challenges of economic inequalities and cultural contestations (Oyedemi, 2021). The narrative journeys of South African emerging adults are thus shaped in a society filled with social complexity, multicultural diversity, continuous transition, sociopolitical concerns, resource constraints, and an unstable economic climate (Alberts & Durrheim, 2018; Du Plessis et al, 2020; Naudé, 2022; Van Lill & Bakker, 2020). South African emerging adults’ identity development is also interwoven with strong ties to African personhood, interconnectedness, spirituality, and family roles and responsibilities (Du Plessis et al, 2020; Naudé & Piotrowski, 2022; Sodi et al, 2021).…”
Section: The Interplay Between Social Media and Identitymentioning
confidence: 99%